The impact of foreign lecturers' recruitment on higher education: An analysis from the Malaysian standpoint - Hoque, K.E.; Alam, G.M.; Shamsudin, F.; Akbar, S.Z.A.; Moktharuddin, R.N.; Fong, Y.S. (Academic Journals, 2010)
This study examined the impact of foreign lecturers' recruitment on the higher education of Malaysia in the following areas: publications in Web of Science journals, competition between local and foreign lecturers in terms of publications, the effectiveness of the teaching and learning process, and world ranking. A qualitative method was used, with data being collected mostly through interviews with local and foreign lecturers, students, and human resource management officials. The study found that the recruitment of foreign lecturers has a significant impact on improving the world ranking of higher education institutions and in increasing publications in Web of Science journals. Also, there was found to be a mixed reaction about their impact on the effectiveness of the teaching and learning process among local teachers and students. The extensive pressure to publish in Web of Science journals has caused the brain drain of experienced senior lecturers and professors. The findings of this study offer valuable information for educational policy makers, vice chancellors, human resource managers, local and foreign lecturers and students.